Linguistic Problems of Arabic Learning in Various Indonesian Formal Schools (2019-2023): A Systematic Literature Review - Muhammad Yahya Abdullah; Alfi Alfarezy; Apri Wardana Ritonga; Mohammad Khalil Mohammad Alramadeen (PPPBA, 2024)
Arabic language learning in Indonesia has become an important part of the formal education curriculum at various school levels. However, this learning process is not free from various linguistic problems that hinder its effectiveness. Students often face difficulties in understanding and using Arabic language correctly, which is influenced by differences in linguistic structures and characteristics between Arabic and their mother tongue. These problems include aspects of morphology, syntax, semantics and phonology, which require special attention so that learning Arabic can run more effectively. This research aims to create a concept map of current linguistic problems in Arabic language learning that occur in Indonesia in the 2019-2023 period. Using a systematic literature review method, this research examines various relevant studies and scientific articles in order to identify and analyze linguistic problems that arise in Arabic language learning at primary, middle and high school and even university levels. The results of this research produce a concept map of linguistic problems which are divided into four main areas: morphology, syntax, semantics and phonology. It is hoped that the concept map resulting from this research can become the basis for more effective learning development strategies and can help educators overcome linguistic problems faced in learning Arabic in Indonesia.